The rain watcher [large type] - Rosnay, Tatiana de, 1961- (Thorndike Press large print basic series., 2018)
"The first new novel in four years from the beloved superstar author of Sarah's Key, a heartbreaking and uplifting story of family secrets and devastating disaster, in the tradition of THE NEST. "Hypnotic, passionate, ominous and tender--unforgettable." --Jenna Blum, New York Times and internationally bestselling author of Those Who Save Us The Rain Watcher is a powerful family drama set in Paris as the Malegarde family gathers to celebrate the father's 70th birthday. Their hidden fears and secrets are slowly unraveled as the City of Light undergoes a stunning natural disaster. Seen through the eyes of charismatic photographer Linden Malegarde, the youngest son, all members of the family will have to fight to keep their unity against tragic circumstances. In this profound and intense novel of love and redemption, De Rosnay demonstrates all of her writer's skills both as an incredible storyteller but also as a soul seeker"--